1976
DOI: 10.1002/bscb.19760850906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 3‐0‐o.coumaryl‐, 4‐0‐o.coumaryl‐and 3‐0‐ferulyl‐d‐(‐)‐quinic acid. Improved synthesis of 3‐0‐sinapyl‐d‐(‐)‐quinic acid

Abstract: The title compounds were obtained by a reaction sequence starting from diphenylmethyl 4,5-0-isopropylidenequina$e. Suitably protected cinnamyl chlorides were condensed with this compound, followed by reaction of the intermediate esters with hydrazine hydrate, and then with acetic acid-formic acid-water. The total yields of 3-0-o. As already mentioned in the foregoing paper ( 5 ) . the synthesis of the title compounds by the method proposed by HASLAM et a2 for the synthesis of e.g. 3-O-p.coumaryl-D-(-)-quinicac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The crude product was esterified following the same protocol as with 1 and purified by column chromatography to give compound 8 in 48% yield. Protection of the hydroxyl group was not necessary since Pooter et al demonstrated that under mild conditions no esterification occurs at the axial C-1 hydroxyl group of quinic acid 27. Deprotection was performed in 6 days in the presence of HCl (2N)/ THF to obtain 5-O-p-coumaroylquinic acid 2a in 77% from the protected ester 8.…”
mentioning
confidence: 99%
“…The crude product was esterified following the same protocol as with 1 and purified by column chromatography to give compound 8 in 48% yield. Protection of the hydroxyl group was not necessary since Pooter et al demonstrated that under mild conditions no esterification occurs at the axial C-1 hydroxyl group of quinic acid 27. Deprotection was performed in 6 days in the presence of HCl (2N)/ THF to obtain 5-O-p-coumaroylquinic acid 2a in 77% from the protected ester 8.…”
mentioning
confidence: 99%